T-shirt airbrushing the step-by-step guide and showcase - Stieglitz, Cliff (Rockport Publishers ; Distributed by North Light Books, 1994)
Nine internationally renowned airbrush artists give step-by-step instruction on their technique. Includes a full-color gallery of finished t-shirts by each artist.